An Analysis of the Rate and Reasons for Rejected Radiographs in Emergency and Non-Emergency Radiology Departments in Yasuj, Iran - Seyyed Amir Moradian; Hamed Zamani; Saman Dalvand (Frontiers in Biomedical Technologies)
Purpose: Utilizing imaging to improve physicians' diagnostic accuracy is one of the primary priorities of radiology departments. When the image is of poor quality, it is likely to be rejected, and its repetition will expose patients and staff to unnecessary ionizing radiation. Given the significant nature of this issue, the current study aimed to evaluate the rate and reasons for radiograph rejections in emergency (public practice) and non-emergency (private practice) radiology departments of Yasuj, Iran.